2014
DOI: 10.1111/apha.12316
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: potential therapeutic targets in diabetic complications of the cardiovascular and renal systems

Abstract: Diabetes mellitus is a serious health problem that can lead to several pathological complications in numerous organs and tissues. The most important and most prevalent organs affected by this disease are the heart and the kidneys, and these complications are the major causes of death in patients with diabetes. MicroRNAs (miRNAs), short non-coding RNAs, have been found to be functionally important in the regulation of several pathological processes, and they are emerging as an important therapeutic tool to avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…2014; Figueira et al. 2014; Pugliese 2014; Kato and Natarajan 2015). Diabetic kidney pathology, especially the initial phase, is not completely understood and more research in this field is relevant to prevent renal deterioration and to reduce mortality in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…2014; Figueira et al. 2014; Pugliese 2014; Kato and Natarajan 2015). Diabetic kidney pathology, especially the initial phase, is not completely understood and more research in this field is relevant to prevent renal deterioration and to reduce mortality in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated an association between miRs and DCM (23)(24)(25). The expression level of miR in the hearts of patients with DCM was found to be different when compared with that of healthy individuals (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…In HK-2 cells, miR-29a acts as a repressor to fine-tune collagen expression and that the reduction of miR-29a caused by high glucose may increase the risk of excess collagen deposition [17]. The potential use of differentially expressed miRNAs may be as novel diagnostic biomarkers and therapeutic targets in DKD [18, 19]. However, the role of miRNA in EMT of HK-2 cells in DKD remains unclear.…”
Section: Introductionmentioning
confidence: 99%